Economic gains from technology-intensive trade: an empirical assessment - Daniels, Peter (1999)
National investment in technological activity is commonly justified in terms of the positive impacts upon productivity, international competitiveness and related aspects of national economic performance. This premise has found a supportive theoretical framework in the new technology and growth models. Based on extended technology-gap models, this study examines cross-country empirical evidence on the relationship between technology-intensive trade performance (as a proxy for technological output) and per capita economic performance, utilising 1978 to 1992 data for around 45 nations. The results provide some support for a positive relationship between trade performance and economic returns. However, the weak and often inconsistent results suggest that the unconditional pursuit of technology-intensive trade improvements may not necessarily have the expected net benefits. - Reproduced
Keywords: Economic growth